Towing Resistance of Otter Trawls used for Shrimps from Small Mechanised Boats - Satyanarayana, A V V; Nair, R S (Fishery Technology, 1964)
Towing Resistance of Otter Trawls used for Shrimps from Small Mechanised Boats